2018
DOI: 10.1038/s41536-018-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Interrupted reprogramming of alveolar type II cells induces progenitor-like cells that ameliorate pulmonary fibrosis

Abstract: We describe here an interrupted reprogramming strategy to generate “induced progenitor-like (iPL) cells” from alveolar epithelial type II (AEC-II) cells. A carefully defined period of transient expression of reprogramming factors (Oct4, Sox2, Klf4, and c-Myc (OSKM)) is able to rescue the limited in vitro clonogenic capacity of AEC-II cells, potentially by activation of a bipotential progenitor-like state. Importantly, our results demonstrate that interrupted reprogramming results in controlled expansion of cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…Early studies using bone marrow MSC faced controversy due to the skepticism that they could truly function as lung epithelium. With the advent of ES and iPS, which can be differentiated in vitro, viable cell sources for use in cell therapy may soon be available [65,129,130,159,163,164]. More studies will need to address the functional integration and long-term regenerative capacity of these cells as well as the safety of engrafted cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies using bone marrow MSC faced controversy due to the skepticism that they could truly function as lung epithelium. With the advent of ES and iPS, which can be differentiated in vitro, viable cell sources for use in cell therapy may soon be available [65,129,130,159,163,164]. More studies will need to address the functional integration and long-term regenerative capacity of these cells as well as the safety of engrafted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limitations and skepticism surrounding MSC, as an alternate source of autologous cells, we have been working on a novel cell type which we have developed by careful dissection of events underlying reprogramming during iPS cell generation. Transient reprogramming with transcription factors Oct4, Sox2, Klf4, and c-Myc (OSKM) resulted in an intermediate product of the iPS cell process which we have termed "induced progenitor-like" (iPL) cells [129,130]. We noted that iPL cells are highly proliferative but retain epigenetic "memory" that allows return to their original identity upon withdrawal of reprogramming factors.…”
Section: Induced Progenitor-like Cells (Ipl)mentioning
confidence: 99%
See 1 more Smart Citation
“…This new method paves the way for future application in humans; for example, by interrupting aberrant reprogramming of alveolar epithelial type 2 cells. Finally, GUO et al [109] have recently demonstrated that a careful reprogramming of AE2C generated induced progenitor-like cells that dampen bleomycin-induced fibrosis when transferred to mice. Of course, whether those promising pre-clinical results will apply to clinical world is elusive, as architectural changes that occurred in IPF lung might themselves preclude stem cell efficacy; also it is likely that stem cells display transient systemic antifibrotic effects through secretion of prostaglandin E2 and IL-10 [110] rather than true effective re-epithelialisation.…”
Section: Targeting Deleterious Developmental Pathwaysmentioning
confidence: 99%
“…The main reason is that the IPF therapeutics lack an effectively targeted carrier or ignore some of the other risk factors such as the instability and tolerability of type II alveolar epithelial cell (AEC II) (5,6). The AEC II, which is considered as "injured" AEC II (7,8) in the IPF tissues, releases excessive amounts of reactive oxygen species (ROS) that initiate an antifibrinolytic coagulation cascade and promote the overexpression of connective tissue growth factor (CTGF) to provoke myofibroblast overactivation and extracellular matrix (ECM) development and then destroy the lung architecture (9)(10)(11). This situation has inspired us to propose that the combination of modulating superoxide in injured AEC II and antimyofibroblast activation as "weeding and uprooting" strategy will be a potential therapeutic strategy for synergistic antifibrosis.…”
Section: Introductionmentioning
confidence: 99%